E-Cigarette Promotion on Twitter in Australia: Content Analysis of Tweets - McCausland, Kahlia; Maycock, Bruce; Leaver, Tama; Wolf, Katharina; Freeman, Becky; Thomson, Katie; Jancey, Jonine (2020)
Background: The sale of electronic cigarettes (e-cigarettes) containing nicotine is prohibited in all Australian states and territories; yet, the growing availability and convenience of the internet enable the promotion and exposure of e-cigarettes across countries. Social media’s increasing pervasiveness has provided a powerful avenue to market products and influence social norms and risk behaviors. At present, there is no evidence of how e-cigarettes and vaping are promoted on social media in Australia.